The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1073/pnas.0409028102
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of hepatitis B virus from the liver of transgenic mice by short hairpin RNAs

Abstract: Hepatitis B virus (HBV) causes acute and chronic hepatitis and hepatocellular carcinoma. Although a preventive vaccine is available, the therapeutic options for chronically infected patients are limited. It has been shown that RNA interference can prevent HBV gene expression and replication in vivo when HBV expression vectors are delivered simultaneously with small interfering RNA (siRNA) or siRNA expression constructs. However, the therapeutic potential of siRNAs to interrupt ongoing HBV replication in vivo h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
135
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(144 citation statements)
references
References 38 publications
3
135
1
Order By: Relevance
“…In addition to the AAV vector used in this study, two recent studies used recombinant adenoviral vectors carrying shRNAs and examined their in vivo silencing effect in similar HBV transgenic mice model. Uprichard et al 20 noted significant suppression of serum HBsAg and HBeAg as well as hepatic HBV transcripts and replicative DNA for at least 20-26 days after injection of 2-5 Â 10 9 PFUs of recombinant adenoviruses expressing HBV-specific shRNAs. The HBV suppression effect was much less significant in another study using adenoviral vectors as shRNAexpressing vehicle, resulting in only 10-fold reduction of HBsAg and two to fivefold reduction of HBeAg and circulating HBV virion in transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the AAV vector used in this study, two recent studies used recombinant adenoviral vectors carrying shRNAs and examined their in vivo silencing effect in similar HBV transgenic mice model. Uprichard et al 20 noted significant suppression of serum HBsAg and HBeAg as well as hepatic HBV transcripts and replicative DNA for at least 20-26 days after injection of 2-5 Â 10 9 PFUs of recombinant adenoviruses expressing HBV-specific shRNAs. The HBV suppression effect was much less significant in another study using adenoviral vectors as shRNAexpressing vehicle, resulting in only 10-fold reduction of HBsAg and two to fivefold reduction of HBeAg and circulating HBV virion in transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…22,51 This concern was actually addressed in one study, which used HBV transgenic mice deficient in IFN-g and IFN-a/b receptor expression to rule out the possibility that HBV suppression was due to the adenoviral vector-induced cytokine effect. 20 Nevertheless, we believe that dsAAV2/8 vector used in this study is a much more appropriate vehicle than adenoviral vector in conducting shRNA studies in HBV transgenic mice. Our result showed that injection of up to 1 Â 10 12 vector genomes of dsAAV2/8 vector did not induce expression of IFN-a/b, IFN-g and TNF-a ( Figure 4), indicating that these previously known HBV inhibitory cytokines were not involved in the RNAi-mediated viral inhibition in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an HBV transgenic mouse model mimicking chronic infection, (Uprichard et al, 2005) have shown that pol III driven siRNA delivered to the liver by recombinant adenovirus suppressed preexisting HBV gene expression and replication for at least 26 days. These results demonstrate the potential of viral vectors for delivery to the liver and long-term RNAi-mediated suppression of target messages when expression systems are used to produce intracellular siRNAs.…”
Section: Rna Interference As a Therapy For Chronic Hepatitis B Virus mentioning
confidence: 99%
“…7 RNA interference (RNAi) therapy using chemically synthesized small interfering RNA and plasmid-or adenovirus-encoded small hairpin RNA (shRNA) have shown promising anti-HBV effects in cell cultures 8,9 and animal models. [10][11][12] However, because of the transient nature of the suppression and the inefficient liver transduction rate, these approaches are unlikely to generate durable anti-HBV effects in more stringent HBV infection conditions, such as in chronically infected patients, as virtually all hepatocytes are infected. We have previously reported generation of a transgenic murine model carrying a complete HBV genome on the ICR mouse background (denoted hereafter ICR/HBV), and demonstrated that, throughout their lifetime, these mice produced consistently high levels of serum HBV DNA, with titers comparable with those found in chronic HBV patients.…”
Section: Introductionmentioning
confidence: 99%